APLIKASI PEWARNAAN GRAF TERHADAP PEMBUATAN JADWAL UJIAN SEMESTER DI JURUSAN PENDIDIKAN MATEMATIKA UNIVERSITAS ISLAM JEMBER - Mahmudah, Muhlisatul; Irawati, Tri Novita (Department of Mathematics Education , University of Jember, 2018)
Abstract. Islamic University of Jember is a private university that organizes education in the Jember city. The implementation of the student exam at Islamic University of Jember, especially Mathematics education, is held 2 (two) times at years, that are the exam in old semester and the exam in even semester. Each exam will be guarded by 1 (one) lecturer, while 1 lecturer can be a examiner for several semester exam in one day, so that in the preparation of the thesis examination schedule must consider the time availability of each lecturer who will test. The preparation of the semester examination schedule at the Islamic University of Jember in mathematics education is manually, so that the overlapping semester exam schedule is still found. The overlapping exam schedule resulted in the implementation of the exam not being maximal, so that a technique was needed in the preparation of the thesis examination schedule. One technique that can be used to form a schedule is vertex coloring graph. The results of this study show that vertex coloring can be applied in making the semester examination schedule by giving better scheduling results than the previous method. The resulting semester exam schedule no longer shows an overlapping exam schedule so that the implementation of the semester exam runs better. Keyword : Scheduling, Vertex Coloring, Exams.